Listeria monocytogenes exploits ERM protein functions to efficiently spread from cell to cell - Pust, Sascha (2005)
Cell-to-cell spread is a fundamental step in the infection cycle of Listeria monocytogenes that strictly depends on the formation of bacteria-induced protrusions. Since Listeria actin tails in the protrusions are tightly associated with the plasma membrane, we hypothesised that membrane–cytoskeleton linkers would be required for initiating and sustaining their formation and the subsequent cell-to-cell spread. We have found that ezrin, a member of the ezrin, radixin and moesin (ERM) family that functions as a key membrane–cytoskeleton linker, accumulates at Listeria protrusions. The ability of Listeria to induce protrusions and effectively spread between adjacent cells depends on the interaction of ERM proteins with both a membrane component such as CD44 and actin filaments. Interfering with either of these interactions or with ERM proteins phosphorylation not only reduces the number of protrusions but also alters their morphology, resulting in the formation of short and collapsed protrusions. As a consequence, Listeria cell-to-cell spread is severely impaired. Thus, ERM proteins are exploited by Listeria to escape the host immune response and to succeed in the development of the infection.